Dendrobium officinale Orchid Extract Prevents Ovariectomy-Induced Osteoporosis in Vivo and Inhibits RANKL-Induced Osteoclast Differentiation in Vitro - Wang, Qi; Zi, Cheng-Ting; Wang, Jing; Wang, Yu-Na; Huang, Ye-Wei; Fu, Xue-Qi; Wang, Xuan-Jun; Sheng, Jun (Frontiers in Pharmacology, 2018)
Background: Dendrobium officinale, a traditional Chinese medical herb with high value that is widely used in Asia, possesses many positive effects on human health, including anti-chronic inflammation, anti-obesity, and immune modulation properties; however, whether Dendrobium officinale has inhibitory effects on postmenopausal osteoporosis remains unknown. Objective: We investigated the effects of Dendrobium officinale extract (DOE) on ovariectomy-induced bone loss in vivo and on osteoclastogenesis in vitro. Methods: In vivo, female rats were divided into a sham-operated (sham) group and five ovariectomized (OVX) subgroups: OVX with vehicle (OVX), OVX with Xian-Ling-Gu-Bao capsule (XLGB; 240 mg/kg body weight/day), and OVX with low-, medium-, and high-dose DOE (150, 300 and 600 mg/kg body weight/day, respectively). Animals in each group were administered their corresponding treatments for 13 weeks. Body weight, serum biochemical parameters, uterine and femoral physical parameters, bone mineral density (BMD), bone biomechanical properties, and bone microarchitecture were obtained. In vitro, the effects of DOE on osteoclastogenesis were examined using RAW264.7 cells. The effects of DOE on osteoclastogenesis and the expression of osteoclast-specific marker genes and proteins were determined. Results: DOE effectively ameliorated serum biochemical parameters, especially alleviated estradiol (E2) deficiency and maintained calcium and phosphorus homeostasis. DOE improved uterine and femoral physical parameters. In addition, DOE improved femoral BMD and biomechanical properties. DOE significantly ameliorated bone microarchitecture. Moreover, DOE inhibited osteoclastogenesis independent of its cytoxicity and suppressed the expression of osteoclast-specific marker genes and proteins. Conclusion: DOE can effectively prevent ovariectomy-induced bone loss in vivo and inhibit osteoclastogenesis in vitro.